Factors predicting PhD affirmation and regret in PhD holders - Radomir Ray Mitic; Enyu Zhou; Hironao Okahana (Humanities & Social Sciences Communications)
Abstract As PhD programmes across disciplines face many questions about return on investment and the many challenges in pursuing the degree, popular discourse surrounding leaving academia has included questions of whether PhD holders regret their PhD. Using a heterogenous choice model, this study shows that despite the many detractors, those who do complete the degree largely affirm their decision. But when examining personal and employment factors including sociodemographics, field of study, job sector, and level of relatedness between the PhD field and field of work, we found that when controlling for how well the PhD prepared individuals for their current employment, background and employment characteristics predicted higher levels of affirmation of the PhD decision in three phases: 1) in general, 2) in the same field, and 3) at the same institution. In particular, this paper found that students of colour were more likely to affirm their decisions perhaps indicating the importance of the credential to the individual but also to the importance individuals place in realizing structural diversity among advanced degree holders across disciplines. These findings illustrate the importance of efforts to improve climate in PhD programmes as well as expanding pathways into careers across sectors.